1980
DOI: 10.1139/b80-179
|View full text |Cite
|
Sign up to set email alerts
|

Control of morphogenesis in the gametophyte of a fern by light and growth hormones

Abstract: The effects of 2,4-dichlorophenoxyacetic acid (2,4-D), gibberellic acid (GA), and abscisic acid (ABA) on the morphogenesis of gametophytes of Lygodium japonicum growing as longer-than-broad biplanar plates in red light and as broader-than-long biplanar plates in blue light were studied. Addition of 2,4-D or GA to the medium induced a change in the form of gametophytes from biplanar to filamentous in red light. Gametophytes growing in a medium containing 2,4-D in blue light were longer than broad, very much lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…The block to antheridium development is especially significant since in this regard ABA acts as an antagonist to the welldocumented antheridiogen system in Ceratopteris. The concentrations at which exogenously supplied ABA is active in Ceratopteris (10-6-104M) are at or well below the levels commonly utilized experimentally in other ferns (Cheng and Schraudolf 1974;Swami and Raghavan 1980) and in angiosperms (Walton 1980 of M or greater are employed. In addition, after growth on ABA supplemented medium for a period of 25 days, meristem and archegonia development are initiated while antheridia development continues to be suppressed.…”
Section: Discussionmentioning
confidence: 89%
“…The block to antheridium development is especially significant since in this regard ABA acts as an antagonist to the welldocumented antheridiogen system in Ceratopteris. The concentrations at which exogenously supplied ABA is active in Ceratopteris (10-6-104M) are at or well below the levels commonly utilized experimentally in other ferns (Cheng and Schraudolf 1974;Swami and Raghavan 1980) and in angiosperms (Walton 1980 of M or greater are employed. In addition, after growth on ABA supplemented medium for a period of 25 days, meristem and archegonia development are initiated while antheridia development continues to be suppressed.…”
Section: Discussionmentioning
confidence: 89%
“…It has been shown that ABA is present in various fern species (Weiler 1979;Cheng and Schraudolf 1974;Yamane et al 1980Yamane et al , 1988Pilate et al 1989) and in some lycophytes. In ferns, ABA plays roles in inhibition of growth (Swami and Raghavan 1980;Chia and Raghavan 1982;Hickok 1983), control of sex determination (Hickok 1983;Warne and Hickok 1991), and heterophyllous switch in aquatic fern plants (Liu 1984;Hsu et al 2001;Lin et al 2005). In addition, ABA is thought to play a role in desiccation tolerance in ferns and lycophytes (Reynolds and Bewley 1993a, b;Pence 2000;Liu et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Like spores, the sensitivity of protonemata (five-to sixcelled stage gametophyte) of ferns to blue, red and far-red light varies greatly. In Lygodium japonicum, gametophytes exhibited planar morphology under red and blue light, but remained filamentous under far-red light (Swami and Raghavan 1980). These light affected growth forms were the result of changed patterns of cell divisions in the protonemata.…”
Section: Resultsmentioning
confidence: 99%